A Salen–Co3+ Catalyst for the Hydration of Terminal Alkynes and in Tandem Catalysis with Ru–TsDPEN for the One‐Pot Transformation of Alkynes into Chiral Alcohols. Issue 6 (11th April 2014) - Wang, Shoufeng; Miao, Chengxia; Wang, Wenfang; Lei, Ziqiang; Sun, Wei
Abstract The cobalt–salen complex (C1:[(salen)Co3+(OAc)]; salen= N, N′‐bis(salicylidene)ethylenediamine, OAc=acetate) was found to efficiently promote the hydration of terminal alkynes to give methyl ketones in the presence of the H2SO4 cocatalyst. In addition, the one‐pot transformation of alkynes into chiral alcohols through tandem catalysis by catalyst C1 coupled with a ruthenium–TsDPEN complex (C3: [(R, R‐TsDPEN)Ru2+(cymene)]; TsDPEN=(1R, 2R)‐N‐(p‐toluenesulfonyl)‐1, 2‐diphenylethylenediamine, cymene=1‐methyl‐4‐(1‐methylethyl)benzene) catalyst was realized with excellent yields and enantioselectivities.